A cross-sectional study on the response abilities of clinical and preventive medical students in public health emergency - Yu, Yao; Qin, Yixuan; Liao, Yuxuan; Yang, Zijiang; Wen, Puqiao; Wu, Jianzhen; Rong, Pengfei (Frontiers in Public Health, 2022)
Inconsistent training programs of public health emergency (PHE) have been criticized as a contributing factor in the PHE emergency managerial weak points. In response, this study analyzed the relevant discrepancies among the medical students in class of 2021 from Xiangya School of Medicine of Central South University by an online questionnaire survey using stratified sampling. The questionnaire comprised four sections including the basic information, the subjective cognition in PHE, the rescue knowledge and capabilities of PHE, and the mastery of PHE regulations and psychological intervention abilities. Related data were collected from 235 medical students dividing into two groups to compare above aspects, namely, clinical medical students (Group A) and preventive medical students (Group B). We found a more positive attitude in PHE (P=0.014) and a better grasp of PHE classification (P=0.027) and reporting system in group B compared with group A. In addition, even if group B showed the same response capability in the communicable diseases as group A did, the former one got less access to clinical practice, resulting in poorer performance in the non-communicable diseases during fire, flood, and traffic accidents (P=0.002, P=0.018, P=0.002). The different emphasis of each training program contributed to the uneven distribution of abilities and cognition. Meanwhile, the lack of integrated PHE curriculum led to unsystematic expertise accordingly. Hence, in order to optimize the PHE emergency management system, equal attention should be paid to the medical students with diverse majors along with a complete integrated PHE curriculum.